Types of Shade Plants As Efforts to Increase Students' Knowledge and Attitudes for Conservation - Eka Haryati Yuliany; Sarno Sarno; Laila Hanum; Sri Parwanti (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2022)
Education carried out for children and adolescents is very important in the formation of community character which is important in the affective aspects of children, cognitive aspects or psychomotor aspects or skills. With this community service, it is hoped that there will be improvements, abilities, and provide scientific information about shade plants that can be used to overcome pollution and support conservation attitudes towards the environment. The method used in this community service is the participatory method. Community service, especially regarding conservation education for students, will ultimately support sustainable development and can have a positive impact on environmental conservation in the present and future.